Direct Hybridization of Polymer Exchange Membrane Surface Fuel Cell with Small Aqueous Supercapacitors1. Issue 3 (29th May 2018) - Ait Hammou Taleb, S.; Brown, D.; Dillet, J.; Guillemet, P.; Mainka, J.; Crosnier, O.; Douard, C.; Athouël, L.; Brousse, T.; Lottin, O.
Abstract: The high power density of polymer exchange membrane fuel cells (PEMFCs) and hydrogen storage may be significantly hampered by the size and weight of the ancillaries needed to control air and hydrogen flow rates and humidity. In order to overcome these difficulties, a variety of research has been carried out on the development of hybrid systems based on supercapacitors or batteries, which raises questions about the best architectures and control strategies and may, if not well mastered, enhance the complexity of the entire system. In this study, we focus on the direct hybridization of PEMFC and supercapacitors (SCs) – using one unit per cell – with the ultimate objective of inserting flat aqueous carbon/carbon SCs within a fuel cell stack. This first experimental work shows that a minimum capacity of about 1 F cm −2 (with reference to the PEMFC active surface) and a maximum series resistance of about 0.5 Ω are sufficient to back up the cell during load variations, such as a sudden increase in the current density: this makes it possible to always supply the fuel cell with the right amount of gas without anticipating current peaks or load transients. Flat supercapacitors were also designed, manufactured and tested during this project; they performed better than commercially available cylindrical supercapacitors of identical capacity, because of a lower series resistance.